Pengaruh Terpaan Social Media Marketing , Sales Promotion , Inovasi terhadap Loyalitas Konsumen dalam Menggunakan Layanan Go-Pay - Nikita Putri Mahardhika; Tandiyo Pradekso (Interaksi Online, 2020)
This study aims to determine whether there is an influence of social media marketing exposure, sales promotion, innovation toward consumers’ loyalty in using Go-Pay as a digital payment. Sample for conducting the research was chosen from Go-Pay users who live in Semarang, aged 20-35 years, have been exposed to Go-Pay’s social media marketing, sales promotion, innovation, and follow @gopayindonesia social media. The collected data were analyzed by the linear regression analysis method. The result indicates that social media marketing exposure did not have any significant influence on consumers’ loyalty in using Go-Pay as a digital payment with a significance level of 0,117. Meanwhile, sales promotion and innovation exposure have a significant influence on consumers’ loyalty. The sales promotion exposure has a significance level of 0,000 with a regression coefficient of 0,170 on consumers’ loyalty. On the other side, innovation exposure has a significance level of 0,001 with a regression coefficient of 0,365.